Maxillary Expansion: A Comparison of Damon Self-Ligating Bracket Therapy with MARPE and PAOO. (9th May 2022) - Alsayegh, Eman; Balut, Nasib; Ferguson, Donald J.; Makki, Laith; Wilcko, Thomas; Hansa, Ismaeel; Vaid, Nikhilesh R.
Abstract : Purpose . The aim of this study was to investigate arch parameters and dentoalveolar changes from pretreatment to posttreatment by comparing the Miniscrew Assisted Rapid Palatal Expansion (MARPE), Periodontally Accelerated Osteogenic Orthodontics (PAOO), and Damon self-ligating bracket therapies. Materials and Methods . Seventy-nine patients underwent maxillary expansion followed by or in conjunction with Damon (n = 23 ), PAOO (n = 28 ), and MARPE (n = 28 ) therapies. Nine maxillary dental arch parameters were compared at pretreatment, posttreatment as well as, increments of treatment change. Measurements were made on STL study casts using 3Shape Ortho Analyzer 3D scanner software. Results . All groups showed significant posterior width increase in the molar area. The mean increase in inter-molar distance was more than 8X greater in MARPE group compared to Damon and more than 4X greater compared to PAOO. MARPE showed significantly greater increments of change in inter-molar width and palatal vault area Conclusions . All groups showed a significant width increase in the canine and molar area. MARPE showed the greatest increase in inter-molar width, followed by PAOO and Damon. MARPE was the only group to show a significant increase in palatal vault area.